Development of A Material Efficiency Assessment Tool for Metal Stamping Product - amed thabit, ahmed wahib (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Aluminium is one of the metals found in this planet and the production of this metal increased which cause increasing of the waste. Moreover, the interest on solid-state recycling of aluminium chips increases over the years due to the less energy consumption of the process, cost saving and less environmental impact. This study investigates the influences of different volume fraction of Boron Carbide and Zirconium Oxide on the aluminium alloy AA6061 physical and mechanical properties. The parameters of volume fraction of B4C and ZrO2 were varied between 5 - 15% and constant temperature on 550 degree and 3 hours respectively. The subject of interest is the physical and mechanical properties which can be obtained through the density and hardness tests. Increasing the volume fraction of and B4C correlates with the increase of composite density. An optimum density was obtained at the volume fraction of B4C and ZrO2 is 5% for the sample extruded at 550 oC and 3 hours duration. The percentage of the volume fraction was revealed to be the most significant factor affecting the microhardness of the composite. It is revealed that the most optimum percentage of volume fraction of B4C is 15% and 5% of ZrO2. To summaries, the solid-state recycling approach using the hot extrusion process generates a significant potential effort for environmental protection and outperforms the traditional recycling method.